Functional Differentiation of Duplicated Flavonoid 3-O-Glycosyltransferases in the Flavonol and Anthocyanin Biosynthesis of Freesia hybrida - Meng, Xiangyu; Li, Yueqing; Zhou, Tongtong; Sun, Wei; Shan, Xiaotong; Gao, Xiang; Wang, Li (Frontiers in Plant Science, 2019)
Flavonols and anthocyanins are two widely distributed group of flavonoids that occurred apart during plant evolution and biosynthesized by shared specific enzymes involved in flavonoid metabolism. UDP-glucose: flavonoid 3-O-glycosyltransferase (UF3GT) is one of the common enzymes, which could catalyze the glycosylation of both flavonol and anthocyanidin aglycons simultaneously in vitro. However, whether and how UF3GT paralogous genes function diversely at biochemical and transcriptional level are largely unknown. Recently, Fh3GT1 was identified to be a member of UF3GTs in Freesia hybrida. However, its expression patterns and enzymatic characteristics could not coincide well with flavonol accumulation. In an attempt to characterize other flavonoid especially flavonol glycosyltransferase genes in Freesia, three closest candidates UFGTs genes - Fh3GT2, Fh3GT3 and Fh3GT4 were mined from Freesia transcriptomic database and isolated from the flowers of the widely distributed Freesia cultivar, Red River®. Based on bioinformatic analysis and enzymatic assays, the Fh3GT2 turned out to be another bona fide glycosyltransferase gene. Biochemical analysis further proved Fh3GT2 preferentially glucosylated kaempferol while Fh3GT1 controlled the glucosylation of quercetin and anthocyanidins. As well, transfection assays demonstrated that Fh3GT2 could be mainly activated by flavonol regulator FhMYBF1 or anthocyanin regulator FhPAP1, whereas Fh3GT1 could only be activated by FhPAP1. These findings suggested that Fh3GTs might have functionally diverged in flavonoid biosynthesis at both biochemical and transcriptional levels.